CAPTURE : Reflections on media images. - Roose, Willem; Andreasen, Kasper (Gent : Koninklijke Academie voor Schone Kunsten, 2011)
Polfliet, Thijs ; Dewaelsche, Rhana ; Ouassala, Wided ; Codron, Devi ; Roose, Willem ; Spiessens, Karen ; Van Daele, Liselotte
CAPTURE, TramZwart, Gent, 12-14 mei 2011
boek